Washington's government : charting the origins of the federal administration - Edling, Max M.; Kastor, Peter J. (University of Virginia Press, 2021)
"This collection of essays investigates the federal government of the United States at its moment of origin, the Washington Administration"-- Provided by publisher.
Keywords: Federal government -- United States -- History -- 18th century.; United States -- Politics and government -- 1789-1797.; États-Unis -- Politique et gouvernement -- 1789-1797.; HISTORY / United States / Revolutionary Period (1775-1800); Federal government; Politics and government; United States; 1700-1799; Essay; essays.; Essays; History; Internet resources.; History.; Essays.; Essais.